2018
DOI: 10.2147/ndt.s170037
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy to improve cognitive dysfunction and encephalatrophy induced by&nbsp;N<sub>2</sub>O for recreational use: a case report

et al.

Abstract: N2O, or laughing gas, is generally used for anesthesia, especially in stomatology and pediatrics but is also commonly used recreationally. Cognitive dysfunction induced by the recreational use of N2O is rare. Here, we present the case of an 18-year-old female with a history of having used N2O recreationally for 5 months who suffered from encephalatrophy and severe cognitive dysfunction. All of the symptoms gradually subsided with ~20 days of treatment by hyperbaric oxygenation. We hypothesize that the long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Six patients were not staying in their country of origin at the time of use and hospitalization, e.g., immigrants and exchange students. One patient [32] was staying abroad during the period of abuse but returned home prior to hospitalization. Of the 31 cases, 15 were female and 16 were male (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six patients were not staying in their country of origin at the time of use and hospitalization, e.g., immigrants and exchange students. One patient [32] was staying abroad during the period of abuse but returned home prior to hospitalization. Of the 31 cases, 15 were female and 16 were male (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This results in a discordance between the treatment of patients with and without neurological symptoms, likely explained by the difference in physicians' awareness of a possible association between psychiatric symptoms and vitamin B12. One of the case reports [32] described a treatment regimen involving hyperbaric oxygen therapy (HBOT), based on the seeming effectiveness of HBOT in cases of delayed encephalopathy after acute carbon monoxide poisoning [63]. The patient in this article presented with various symptoms, including tetraparesis, disturbance of orientation and memory, and irritability.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of HBOT on the cognitive dysfunction induced by nitrous oxide abuse is unknown. We previously reported the improvement of cognitive function with HBOT in a patient who abused nitrous oxide 11. Based on this finding and the literature regarding the improvement of cognitive function with HBOT, we plan to conduct a randomised, double-blinded, placebo-controlled trial to investigate the effect of HBOT on cognitive dysfunction in patients who abuse nitrous oxide.…”
Section: Introductionmentioning
confidence: 95%
“…They presented deficits in attention, executive functioning, short-term memory and visuospatial organisation, and the symptoms slowly improved after the cessation of occupational exposure and treatment with antidepressants and neuropsychology 10. In addition, recent cases also reported that nitrous oxide abuse may cause cognitive dysfunction;11 12 however, the characteristics of cognitive impairment due to nitrous oxide abuse are unknown.…”
Section: Introductionmentioning
confidence: 99%